Business resilience in turbulent times on Ukraine's example - Taranishyn, Andrii; Kubíček, Aleš; Bruder Badie, Natálie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Business resilience is a combination of characteristics, abilities, capacities or capabilities that allows an organization to withstand known and unknown disturbances and still survive. Ukrainian business operation in the current wartime environment is a perfect case to study resilience. The aim of the thesis is to provide first-hand examples of Ukrainian businesses that adapted to the stressful and turbulent environment, and explore the ways in which they adapted, tweaked or changed their business model to stay afloat and continue operations. It also aims to bridge the knowledge gaps such as relationship between personal attributes and company resilience, the effect of company size on its resilience, and to explore experiences of Ukrainian companies in a longer timeframe. It uses a qualitative approach based on semi-structured interviews. The findings show that resilient people create resilient organizations, the small size negatively impacts business resilience, and outline some unexpected novel findings about wartime business specifics.
Vedoucí práce: Aleš Kubíček
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses